A theory of distributional violence: an analysis of proxy wars in Africa, 1945-2011 - Rauta, Vladimir (2017)
This thesis addresses three questions: What are proxy wars? How are proxy wars waged? Why are proxy wars waged? Each research question addresses a gap, a flaw or a deficiency in the current knowledge of proxy wars. Accordingly, each question is matched with a research aim. The first aim is to establish a conceptual and definitional baseline for proxy wars as a point of inquiry. The second seeks to restrict the empirical domain of proxy wars in an effort to enhance our ability to recognise proxy wars in the contemporary security environment. Lastly, the third objective is an analysis of the normative and causal dynamics underpinning party interaction in proxy wars. Taken together, the three research questions form the focus of my research, namely to understand and explain proxy wars as a self-standing form of political violence. I apply my research questions to Africa on a timeline beginning with 1945 leading up to 2011. I build a qualitative dataset, the Proxy War Dataset, which maps the spread of the phenomena across time, space (regions, countries), and conflict indicators (incompatibility). I use it as a descriptive tool to understand proxy wars, as well as a theory-informing source of data. In answering the causality problem, I put forward a theory of distributional violence focused on strategic interaction which yields four distinct logics of distribution of violence in proxy wars: pre-emptive, managerial, retaliative, and cooperative. I probe the theory with a series of four case studies focused on proxy wars in Ethiopia, the country most affected by the phenomena under observation throughout the 1945-2011 timeline.